YENİDOĞAN PNÖMOTORAKSLI OLGULARDA MORTALİTE VE MORBİDİTENİN DEĞERLENDİRİLMESİ - İLÇE, Zekeriya and GÜNDOĞDU, Gökhan and ILIKKAN, Barboros and CELAYİR, Sinan (Cerrahpaşa Medical Journal, 2019)
Background and Design.- Newborn pneumothorax is a frequently seen condition in mechanically and manually ventilated neonates. However in some cases etiology for the pathology remains unclear. We retrospectively reviewed patients who were hospitalized for pneumothorax in two different neonate intensive care units. Material and methods: Between 1996 and 2001 83 cases were analyzed according to gestational age, weight, underlying primary lung pathology, age of admittance, side of pneumothorax, drainage time, need for mechanical ventilation. These criteria were assessed with mortality. 8 or 10 Fr feeding tube or pleurocan were used for thorax drainage. For diagnosis chest x-ray films were used. Compute tomography was used to eliminate congenital anomalies from pneumothorax in some patients. Results.- 83 neonates were assessed. M: F ratio was 1.6:1 Mean age of admittance was 63.8 hours (2 hours-20 days). 51 patients (61.4%) have low birth weight (less than 2500g). 41 patients (% 49.4) have prematurity. Patients weight ranged between 640 and 5170g. (Mean: 2280), 51 patients (% 61.4) needed mechanic ventilation. Pneumothorax was in right hemithorax in 44 (53%) patients, in left hemithorax 21 patients (25.7%) and 18 patients (21.7%) were bilaterally affected. We were able to define the underlying lung pathology in 49 patients (59%). 32 (38,6%) babies died. In those cases side of pneumothorax is respectively, bilateral in 13 cases (40.7%), right side in 12 cases (37.5%) and left side in 7 cases (25.3%). 22 (68%) of these lost babies were premature. We found underlying lung pathology in those 24 lost babies (75%) and 29 (90.6%) of them needed mechanic ventilation. Thorax tubes were stayed in 1-23 days (Mean 7.5 day). The mean hospital stay was 12,7 days (1-64). The difference in mortality was statistically non significant between the side of pnomothorax but significant in the presence of primary lung disease, low birth weight, prematurity and use of mechanical ventilation (p<0,005). Conclusion.- In neonate pneumothorax cases; low birth weight, prematurity, mechanic ventilation and underlying primary lung disease increases the mortality and morbidity.